Promising medical therapies for Parkinson’s disease - Hauser, Robert A. (Henry Stewart Talks, 2014)
Selected Future Therapies for Motor Fluctuations and Dyskinesias, Ankiparkinsonian agents, A2a antagonists, Levodopa preparations, VR040 (inhaled apomorphine), Safinamide (mixed MOA : MAO-B and glu inhibition), Anti-dyskinetics, AFQ056 : mGluR5 antagonist, ADX48621 (dipraglurant) : mGluR5 negative allosteric modulator, Fipamezole :a2 adrengergic receptor antagonist, ADS-5102 : sustained release amantadine